2020
DOI: 10.3390/pr8070756
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance Enhancement in Flat Plate Solar Collector Solar Water Heater: A Review

Abstract: Various studies to improve the thermal performance of flat plate solar collector (FPSC) solar water heater have been conducted, and more are currently in progress. This study aims to review existing methods on thermal performance enhancement for FPSC and discuss on heat-transfer enhancement using vibration and its potential application for FPSC. Ten methods for improving thermal performance are identified, which include applications of nanofluids, absorber coatings, phase change materials (PCM), thermal perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Table 6 lists some recommendations from this review for future research based on previously conducted studies that have explored collector materials and geometric design. [ 50,179,180 ]…”
Section: Swh Specifications and Characteristicsmentioning
confidence: 99%
“…Table 6 lists some recommendations from this review for future research based on previously conducted studies that have explored collector materials and geometric design. [ 50,179,180 ]…”
Section: Swh Specifications and Characteristicsmentioning
confidence: 99%
“…It was previously reported that the collector's design has a signi cant impact on its thermal performance (Shukla et al, 2013). The thermal performance of a at plate collector is in uenced by several essential elements (Ikmal et al, 2020). These elements include ow tube, absorber plate and glazing cover.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in nanoparticle concentrations enhanced the thermal energy gain and led to an increase in the fluid outlet temperature. Shamsul Azha et al [12] presented a study that includes a review of ten methods for improving the heat transfer using vibration and its possible application to flat plat solar collector. These include: the use of nanofluids, absorbent coatings, (PCM), thermal performance enhancers, FPSC design modifications, the use of polymeric materials, heat loss reduction, mini-channel and micro-channel, and enhanced heat transfer using vibration.…”
Section: Introductionmentioning
confidence: 99%